Research on characteristics of embedded resonator sensor based on PtS2 - Li, Xin; Li, Xieyuan; Zhang, Haitao; Chen, Shuang; Liu, Shurong; Li, Yang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
An embedded microring resonator model using PtS2 as the core layer was designed and optimized for sensing. The inner layer is made of PtS2, and SiO2 and Si3N4 are used as cladding. The overall structure is Si3N4-SiO2-PtS2-SiO2-Si3N4. Field strength distribution of longitudinal section of single straight waveguide and the longitudinal section of coupling part of straight and annular waveguides are simulated according to the coupled-mode theory. The transfer matrix method is used to analyze characteristics between the length of the U-shaped feedback waveguide and the circumference of microring and the change of attenuation factor and coupling coefficient on the output spectrum. The simulation results showed that the embedded microring resonator with PtS2 as the core presents excellent optical properties. The resonance depth is more than –50 dB, and the sensitivity can reach 1806.61 dB/RIU. When the resonance wavelength is 1550.86 nm and the self -coupling coefficient is 0.9849. The corresponding detection limit is about 1.66056 × 10–7 dB/RIU, and the quality factor is 2.8848 × 10–5 under the measurement system with a signal-to-noise ratio of 30 dB. Compared with the traditional single microring structure, the proposed microring presents a higher free spectral range and more suitable for the fabrication of high-sensitivity, low-detection limit, and large-measurement range sensors.
Optica Applicata, Vol. 53, 2023, nr 2, s. 213-226
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; PtS2 core layer; U-shaped feedback waveguide; embedded; microring resonator